Performance analysis of a 10-MW wind farm in a hot and dusty desert environment. Part 2: Combined dust and high-temperature effects on the operation of wind turbines. (October 2021) - Al-Khayat, Mohammad; Al-Rasheedi, Majed; Gueymard, Christian A.; Haupt, Sue Ellen; Kosović, Branko; Al-Qattan, Ayman; Lee, Jared A.
Abstract: High temperatures and dust accumulation can impact wind turbine performance and increase the maintenance burden and operating cost of wind turbines in desert regions. A novel, detailed analysis method is presented to quantify the separate and total effects of these adverse conditions on the performance of each 2-MW turbine of the 10-MW Shagaya wind farm in Kuwait. Using two years of operational data, it is found that dust accumulation on the ventilation systems and equipment inside the nacelle leads to an early start of the turbine's power derating during high-temperature periods. During the first few days after cleaning, the energy loss is entirely caused by high temperatures. After that, dust accumulates and the energy losses resulting from the combined effects of dust and heat increase. A higher cleaning frequency is found to significantly decrease dust-induced losses. It is also found that temperatures in the range 40–44 °C contribute most to losses affecting the total energy production. The total annual high-temperature energy losses are only ≈1.2%, whereas dust accumulation induced energy losses that increased from 0.31% per turbine in the first year to 1.45% per turbine in the second year. The plant's dust cleaning strategy still needs to be optimized.